The Search for the Objective Truth and Moral Certainty of the Judge In the Canonical Process of Marriage - MIERZEJEWSKI, KRZYSZTOF (Prawo Kanoniczne, 2013)
The legal proceeding which also contains the canonical process concerning the statement of an annulment of marriage aims to establish the objective truth. The Judge should have the moral certainty which is necessary and sufficient at the same time to establish the truth. This article aims to show the connection between these notions, the difference between moral certainty, probability and absolute certainty. This article also discusses those elements in Canon Law which help one to gain moral certainty, as well as revealing the objective truth. This article is intended as a help in a scholarly investigation of the canonical processes concerning marriage.